Using BIM as a lean management tool in construction processes – A case study - Ahmed.M. Eldeep; Moataz.A.M. Farag; L.M. Abd El-hafez (Ain Shams Engineering Journal, 2022)
One of the most important reasons that may result in poor performance in Architectural, Engineering, and Construction (AEC) is to create a visualization of construction processes and poor exchanging of information between different work teams. Lean construction seeks to reduce and eliminate waste in the construction processes, while BIM seeks to improve collaboration between project team members.This paper investigates BIM as a lean tool in the construction processes with a case study by concentrating on understanding the interactions between the design and implementation processes. The research demonstrates that BIM can detect errors, omissions, and clashes before construction, which helped reduce waste and make the construction processes more linear. BIM helped to minimize the design time to nearly 50% and supports prefabrication and installation activities to save up to one and a half months during execution by removing the waiting time wastes through construction processes. Alternatively, the BIM model can help reduce the number of change orders and RFI's; About 11% of increasing the total contract price and 25% of increasing the total contract time could be avoided by using BIM as a lean construction process tool.